The tadpole of Bokermannohyla lucianae (Napoli & Pimenta 2003) (Amphibia, Anura, Hylidae) - Mercês, Ednei De Almeida; Camurugi, Felipe; Barreto, Gilvana Santos; Solé, Mirco; Juncá, Flora Acuña (Zootaxa, 2015)
Bokermannohyla lucianae (Napoli & Pimenta 2003) belongs to the Bokermannohyla circumdata species group (Faivovich et al. 2005) that currently contains 19 species: B. ahenea (Napoli & Caramaschi 2004), B. astartea (Bokermann 1967), B. capra Napoli & Pimenta 2009, B. caramaschii (Napoli 2005), B. carvalhoi (Peixoto 1981), B. circumdata (Cope 1871), B. feioi (Napoli & Caramaschi 2004), B. gouveai (Peixoto & Cruz 1992), B. hylax (Heyer 1985), B. ibitipoca (Caramaschi & Feio 1990), B. izecksohni (Jim & Caramaschi 1979), B. lucianae (Napoli & Pimenta 2003), B. luctuosa (Pombal & Haddad 1993), B. nanuzae (Bokermann & Sazima 1973), B. napoli Carvalho, Giaretta & Magrini 2012, B. ravida (Caramaschi, Napoli & Bernades 2001), B. sagarana Leite, Pezzuti & Drummond 2011, B. sazimai (Cardoso & Andrade 1982), B. vulcaniae (Vasconcelos & Giaretta 2005). Although species of this group are usually related to altitudinal riparian environments within the Atlantic Forest biome (Napoli & Pimenta 2009), some species occur near to the sea level (e.g. B. capra and B. lucianae) (Camurugi et al. 2010, Dias et al. 2011). Until now, tadpoles of 11 species of the B. circumdata species group have been formally described (Gaiga et al. 2013, Mongin & Carvalho-e-Silva 2013). Herein we describe the previously unknown tadpole of B. lucianae and compare it with tadpoles of other species of the group.